Seasonal Incidence of Insect Pests of Mustard (Brassica juncea L.) and their Correlation with Weather Parameters: MUSTARD INSECT PEST INCIDENCE AND WEATHER PARAMETERS - Akshay Kumar Singh Pratihar; Dr. M.M. Sundria; Pandey, Dr. Shalini; Dr. Rahul bhardwaj (Annals of Arid Zone, 2024)
Seasonal Incidence of mustard insect pests and their correlation with weather parameters has been studied under field conditions at Research Farm, Agricultural Research Station, Mandor, during Rabi season, 2021-22. The results revealed that aphid, Lipaphis erysimi (Kalt.) infestation initiated from 51st Standard Meteorological Week (SMW) and reached at peak (126.20 aphid/10 cm terminal shoot) on 4th SMW while the painted bug, Bagrada hilaris (Kirk.) infestation was observed two times in the cropping season. First infestation was observed in 45th SMW (0.60 bugs/plant) and second infestation occurred from 8th SMW to 10th SMW (5.13 bugs/plant). Likewise, the flea beetle, Phyllotreta cruciferae (Goeze)  peak activity was noticed on 4th SMW (0.93 beetles/plant) whereas the leaf webber, Crocidolomia binotalis Zell. infestation reached to peak (2.87 larvae/plant) on 6th SMW. Mustard aphid was  significantly negative correlated with minimum temperature while  significantly positive with morning relative humidity (RH). Flea beetel and leaf webber were significantly negative correlated with minimum temperature. Painted bug was significantly positive with maximum temperature while significantly negative correlated with evening RH.